HUBUNGAN STATUS NUTRISI DENGAN KEJADIAN DISMINORE PADA REMAJA - Permanasari, Ika; Azizah, Nila; Yanti, Rifa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Dysmenorrhea causes most women to be unable to move normally, as well as the incidence of dysmenorrhea experienced by adolescents can cause difficulty concentrating in learning and decreased learning motivation, imbalances in nutritional status in adolescents will affect the growth and development of organs. This will also affect reproductive function and affect pain during menstruation. The purpose of this study was to determine whether there is a relationship between nutritional status and the incidence of dysmenorrhea in adolescent girls at SMA Negeri 2 Siak. Methods: This type of research was quantitative with a cross-sectional research design. This research was conducted in February – July 2023. The sample in this study amounted to 91 of 118 populations taken by simple random sampling technique, data analysis using a correlation test with Kolmogorov Smirnov. Result: The results of the study found that the majority of Young Women were in grade 10, the average age of Young Women was 17 years, the average experienced menarche at the age of 12 years, the majority of Young Women experienced dysmenorrhea 81.4% and 54,9 % the majority of Young Women had underweight nutritional status. The results of statistical tests obtained there are a relationship between the status of nutrition and the incidence of dysmenorrhea (p value 0.000 < 0,05). Conclusion: Nutritional status in adolescent girls has a relationship with the incidence of dysmenorrhea perceived during menstruation. It is expected that adolescents understand the importance of nutritional intake at adolescence because nutritional status will affect the occurrence of menstrual disorders such as dysmenorrhea.Keywords: Dysmenorrhea, Adolescence girl, Nutritional Status